THE DEVELOPMENT OF LEARNING MEDIA HANDBOOK DESCRIPTIVE TEXT TO IMPROVE STUDENTS’ WRITING SKILL - Wulandari; Harahap, Anna Leli; Rusli, Muhammad (Journal of English Education and Linguistics, 2024)
The objective of this study is to describe how to develop learning media handbook descriptive text to improve students’ writing skill at tenth grade SMK SwastaSitiBanunSigambal. This research and development use the ADDIE model research procedure by Borg and Gall. There are five stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The data were obtained from a validation sheet and a questionnaire. The result data used quantitative and qualitative data analysis techniques. The results showed that there was no use of a specific Descriptive Text Handbook with writing skills in schools. Schools only use textbooks that contain all learning competencies and have never used a special handbook containing one learning competency. The results of the validation of this handbook are the results from media experts score 35, percentage 87,5%, very valid category, the validation results from the material expert, the score was 36, percentage 90 %, very valid, the result of the student’s validation, the score was 1236, the percentage was 85,8%, the category was very valid, so it was declared the book was suitable for use.